Bibliographical Review About Quality Cost Management Systems in the Moroccan Market - Jabri Wijdane; Ayach Lamiaa; Moustaid Khadija (International Journal of Supply Chain Management, 2022)
Quality management (QM) has become an undeniable issue for companies of different sizes, given all the advantages it offers them in terms of competitiveness in the international market. It boosts brand image and authorities’ confidence in the organization’s practices. However, quality cost management system (QCMS) is not practiced as much due to several factors. This article presents the works done on QCMS in the Moroccan Market and shows the beneficial impact on the strategy and sustainability of companies.